Nilai-Nilai Holistik dalam Kaunseling Islam: The Holistic Values of Islamic Counselling - Rajab, Khairunnas (Afkar: Jurnal Akidah dan Pemikiran Islam, 2015)
Islamic counselling is a paradigm describes the holistic values ​​of Islam in the services and assistance to clients, and as a theoretical-practical alternative solution to the problems concerned with human health interests. Islamic counselling is a form of knowledge based on Islam in the discipline of Counselling Psychology, in which it portrays the comprehensive aspects of emotional spiritual intuitive. From the beginning, when the Prophet Muhammad p.b.u.h delivered the message of prophecy, he was shaping and colouring the fields of counselling through advice and guidance on issues affecting the Muslim community at the time. In this decade, Islamic counselling has become one of the research focuses in the Islamization of sciences, as efforts to integrate science with Islam. Islamic counselling can be expressed as the services and assistance for clients who are suffering from psychological problems by using the services and assistance of systematic Islamic counselling. Integration of spiritual aspect has been offered by Islamic counselling that includes faith, piety, ihsan, consistency, honesty, balance and openness that are the foundations in the process of counselling. This article aims to explain the theoretical-practical Islamic counselling that can be proposed as an alternative in solving social psychological problems of Muslims in the modern century.